Penegakan Hukum Bagi Wna Yang Mengendarai Sepeda Motor Sewa Tanpa Sim Secara Ugal-Ugalan (Studi Kasus: Polsek Kuta Utara) - I Nyoman Gede Sugiartha; I Gusti Agung Istri Arinda Praminingrat; Anak Agung Sagung laksmi Dewi (Jurnal Analogi Hukum, 2025)
Traffic is everything related to travel from one place to another, bound by the provisions of Law Number 22 of 2009 concerning Road Traffic and Transportation. As time goes by, tourism in Bali begins to reach its peak, resulting in more and more foreigners or foreign nationals visiting Bali for their own needs, many also rent motorbikes to get around Bali, but cases of foreigners riding motorbikes are increasing. . increase. careless. The formulation of the problem in this research is: 1) What factors cause foreigners to ride motorbikes recklessly on the highway? 2) What are the obstacles to law enforcement for foreigners who ride motorbikes carelessly on the highway? This research has general and specific objectives, and is equipped with research uses seen from theoretical and practical uses. This research uses empirical legal research methods. Based on the research results, it can be concluded that the factors causing reckless foreigners are: human factors, road facility factors, vehicle factors and natural condition factors. Then the obstacles to law enforcement for foreigners driving reckless motorbikes on the highway are internal enforcement from the police and external obstacles from the community.